Improving sperm quality and spermatogenesis through a bioactive marine compound: an experimental study - Lorenzetti, A.; Marotta, F.; Yadav, et al., H. (Acta Biomedica Atenei Parmensis, 2012)
Dietary lipids may affect sperm membrane structure, fluidity and its susceptibility to oxidative phenomena which may lead to altered sperm viability and proper binding to eggs.Given the recently demonstrated beneficial effects of fish oil diets on turkey fertility and embryo viability, the aim of this study was to test a caviar-derived marine product on spermatogenesis and sperm quality. Sixty mice were divided into four different groups and fed for 3 weeks with normal chow (group A), added with LD-1227 at the dosage of either 5 mg/day (B1) or 10 mg/day (B2) while Group C received standard chow added with 10 mg of a DHArich mixture. At sacrifice tests/body weight ration and spermatogenesis was checked. No toxicity, histological sign or body or testes growth abnormality was noted, irrespective of the treatment. As compared to control, all supplements showed to increase sperm counting and motility although the effect of LD-1227 10 mg was significantly higher than DHA alone (p